2018
DOI: 10.1115/1.4040187
|View full text |Cite
|
Sign up to set email alerts
|

Custom-Fit Three-Dimensional-Printed BiPAP Mask to Improve Compliance in Patients Requiring Long-Term Noninvasive Ventilatory Support

Abstract: Noninvasive ventilator support using bi-level positive airway pressure/continuous positive airway pressure (BiPAP/CPAP) is commonly utilized for chronic medical conditions like sleep apnea and neuromuscular disorders like amyotrophic lateral sclerosis (ALS) that lead to weakness of respiratory muscles. Generic masks come in standard sizes and are often perceived by patients as being uncomfortable, ill-fitting, and leaky. A significant number of patients are unable to tolerate the masks and eventually stop usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 13 publications
(18 reference statements)
0
13
0
Order By: Relevance
“…Among several other groups ( 7 , 8 ), we are currently developing a research platform to personalize NIV masks using ultrarapid 3D scanning and printing techniques, which may in the future be exploited also in the acute phase of critical illness in the PICU. Wu et al have reported the development of custom-fitted masks for long-term NIV in adult patients with sleep apnoea or neuromuscular disease using stereolithography 3D printing and magnetic resonance imaging (MRI) data ( 7 ). In addition, Willox et al workers have tested the feasibility of different designs of 3D printed, customized masks in adult volunteers, to inform future development and implementation in pediatric patients ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among several other groups ( 7 , 8 ), we are currently developing a research platform to personalize NIV masks using ultrarapid 3D scanning and printing techniques, which may in the future be exploited also in the acute phase of critical illness in the PICU. Wu et al have reported the development of custom-fitted masks for long-term NIV in adult patients with sleep apnoea or neuromuscular disease using stereolithography 3D printing and magnetic resonance imaging (MRI) data ( 7 ). In addition, Willox et al workers have tested the feasibility of different designs of 3D printed, customized masks in adult volunteers, to inform future development and implementation in pediatric patients ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The need for personalized NIV masks is currently widely recognized, although potential strategies have mostly focused on long-term use in adults or children in home settings (7)(8)(9)(10)(11). Commercially available non-vented pediatric NIV masks are limited in their range of dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…With continued frustration, patients elect to discontinue their use, and ultimately, the intended treatment cannot be delivered. One study examined the effects of custom fitting BiPAP/CPAP for one patient; the participant described improvement in the majority of the custom-made masks, and most notably noted the comfortability of the fits [ 130 ]. These findings, though only in a single patient study, are promising and pave the way for future use in creating comfortable, appropriate masks that are easy for patients to use consistently.…”
Section: Current Applications In Medicinementioning
confidence: 99%
“…These interfaces are described as more comfortable, leading to less skin lesions and having the potential to increase ventilation efficacy ( 22 24 ). The growing availability of 3D medical printing leads to the development of 3D-printed custom masks for adults and children ( 25 , 26 ).…”
Section: Interfacesmentioning
confidence: 99%